(untitled) (The Pretoria Student Law Review, 2023)
In this reflection I draw on the PLSR Editorial Board’s experiences to broadly think about our understanding of community within the university, and beyond. The purpose of this reflection is to remind readers of the PSLR’s significance and potential, and to encourage a radical rethinking of the type of university community we nurture.